Non-tuberculous mycobacterial keratitis: a study of 22 cases. - Huang, S C (1996)
AIM: To investigate causes and clinical findings of non-tuberculous mycobacterial keratitis, and to study its response to topical antibiotic therapy and surgical extirpative keratectomy. METHOD: A single centre, retrospective review of 22 patients with non-tuberculous mycobacterial keratitis seen in a 3 year period. Laboratory diagnoses were established with Ziehl-Nielsen acid fast staining and Löwenstein-Jensen cultures. RESULTS: In 20 patients (91%), there was an antecedent history of foreign body eye trauma (18 patients) or elective surgery (two patients). There were 19 cases of Mycobacterium chelonei, and three of M fortuitum. Clinical signs included epithelial defects, satellite or ring stromal infiltrates, crystalline keratopathy, and hypopyon. For topical antibiotic therapy, 20 patients received amikacin, while one patient received rifampin and another received ciprofloxacin, each in accordance with the results of the in vitro drug sensitivities. An extirpative keratectomy was performed in 15 cases; four of these cases additionally required a temporary conjunctival flap in order to finally eradicate the infection. At the end of the follow up period (median 18 months; range 3 months to 3 years) all eyes were stable and free of infection, with 19 (86%) having final visual acuities of 20/200 or better. CONCLUSION: Early clinical recognition and prompt laboratory diagnosis, together with aggressive topical antibiotic therapy and early keratectomy, may shorten morbidity and improve the clinical outcome of non-tuberculous mycobacterial keratitis.